Muscle fiber types and training - Karp, J. R.
Your athletes' fiber type proportion will playa major role in the amount of weight that they can lift, the number of repetitions that they can complete in a set or interval workout, and the desired outcome (increased muscular strength/power or endurance). For example, an athlete with a greater proportion of fast- twitch fibers will not be able to complete as many repetitions at a given relative amount of weight as will an athlete with a greater proportion of slow-twitch fibers and therefore will never attain as high a level of muscular endurance as will the ST -fibered athlete. Similarly, an athlete with a greater proportion of ST fibers will not be able to lift as heavy a weight or run intervals as fast as will an athlete with a greater proportion of FT fibers and therefore will never be as strong or powerful as will the FT - fibered athlete. It is important to remember that, even within the group of sprinters or distance runners on your team, there will still be a disparity in the fiber types. Not all the sprinters will have the same percentage of FT fibers, nor will all the distance runners have the same percentage of ST fibers. Therefore, some sprinters may be able to complete 10x200 meters in a workout while others are fatigued after 8 repetitions. Likewise, some distance runners may be able to complete 8x800 meters, while others may fatigue after 5 repetitions. Depending on each particular athlete, the coach should decide whether those who fatigue sooner (because of more FT fibers) should be given longer rest periods between intervals in order to complete the workout, or should run fewer repetitions at a faster speed. Training a FT -fibered muscle for endurance will not increase the number of ST fibers, nor will training a ST-fibered muscle for strength and power increase the number of FT fibers. With the proper training, FT -B fibers can take on some of the endurance characteristics of FT -A fibers and FT -A fibers can take on some of the strength and power qualities of FT-B fibers. However, there is no inter-conversion of fibers. FT fibers cannot become ST fibers, or vice versa. What an athlete is born with is what he or she must live with. Although the type of fiber cannot be changed from one to another , training can change the amount of area taken up by the fiber type in the muscle. In other words, there can be a selective hypertrophy of fibers based on the type of training. For example, an athlete may have a 50/50 mix of FT/ST fibers in a muscle, but since FT fibers normally have a larger cross-sectional area than ST fibers, 65% of that muscle's area may be FT and 35% may be ST. Following a strength training program for improvement in muscular strength, the number of FT and ST fibers will remain the same (still 50/50), however the cross-sectional area will change. This happens because the ST fibers will atrophy (get smaller) while the FT fibers will hypertrophy (get larger). Depending on the specific intensity used in training, the muscle may change to a 75% FT area and a 25% ST area. The change in area will lead to greater strength but decreased en- durance capabilities. In addition, since the mass of FT fibers are greater than that of ST fibers, the athlete will gain mass, as measured by the circumference of the muscle. Conversely, if the athlete trains for muscular endurance, the FT fibers will atrophy while the ST fibers hypertrophy, causing a greater area of ST fibers. The area of the muscle, which began at 65% FT and 35% ST before training, may change to 50% FT and 50% ST following training, The endurance capabilities of the muscle will increase while its strength will decrease, and the athlete will lose some muscle mass, again be- cause ST fibers are lower in mass than FT fibers. The decrease in mass may be observed by a smaller circumference of the muscle. Many coaches know that, for gains in muscular strength, one should train with heavy weights and few repetitions. This training regimen works because using heavy weights recruits the FT -B fibers, which are capable of producing a greater force than the ST or FT -A fibers. Hypertrophy will only occur in those muscle fibers that are overloaded, so the FT - B fibers must be recruited during training in order to be hypertrophied (Morehouse & Miller, 1976). Training with a low or moderate intensity will not necessitate the recruitment of the FT -B muscle fibers. Therefore, the training intensity must, be high. But how heavy a weight and how many repetitions should you use? Muscular strength is primarily developed when an 8-repetition maximum (8RM, the maximum amount of weight that can be lifted eight times ) or less is used in a set. When the aim of training is to increase the neuro- muscular component of maximum strength, at least 95% of the athlete's 1RM and 1 to 3 repetitions should be used. When the aim is to increase maximum strength by stimulating muscle hypertrophy, at least 80% of 1RM should be lifted 5 to 8 times or until failure (Zatsiorsky, 1995). This latter recommendation assumes that the focus of training is hypertrophy for strength, rather than hypertrophy simply for muscle size. If the aim of training is to increase muscle size (hypertrophy) with moderate gains in strength, then 6 to 12 repetitions should be used (Fleck & Kraemer, 1996). Remember, in order to improve muscular strength, FT -B fibers must be recruited. For maximum results, train your athletes according to their genetic predisposition. For example, an athlete with a greater proportion of slow- twitch fibers would adapt better to running more weekly mileage and a muscular endurance program, using more repetitions of a lighter weight. Likewise, an athlete with a greater proportion of fast-twitch fibers would benefit more from sprint training and a muscular strength program, using fewer repetitions of a heavier weight.